Influence of nitrogen on CO-laser characteristics - Grigorian, Galina M.; Cenian, Adam (Photonics Letters of Poland, 2017)
The role of the addition of nitrogen to the discharge plasma of CO lasers on plasma-chemical processes is discussed here. It is shown that nitrogen addition improves laser characteristics and changes the composition of the laser active medium. A reduction of CO highly-excited vibrational-states populations with current is smaller in the case of mixtures with nitrogen additions. The addition of nitrogen significantly decreases CO dissociation level and concentrations of C atoms created in plasma-chemical reactions of laser discharge. Full Text: PDF References G.M. Grigorian and I.V. Kochetov, "Balance of CO molecules in the plasma of a sealed-off CO laser", Plasma Phys. Rep. 30, 788 (2004). CrossRef V.S. Aleinikov and V.I. Masychev, CO Lasers (Moscow, Radio i Svyaz’ 1990). A. Cenian, A. Chernukho, V. Borodin and G.Śliwiński, "Modeling of Plasma-Chemical Reactions in Gas Mixture of CO2 Lasers I. Gas Decomposition in Pure CO2 Glow Discharge", Contr. Plasma Phys. 34, 25 (1994). CrossRef A. Cenian, A. Chernukho, V. Borodin, "Modeling of Plasma-Chemical Reactions in Gas Mixture of CO2 lasers. II. Theoretical Model and its Verification", Contrib. Plasma Phys. 35, 273 (1995). CrossRef A. Cenian, A. Chernukho, P. Kukiełło, R. Zaremba, V. Borodin and G. Śliwiński, "Improvement of self-regeneration of gas mixtures in a convection-cooled 1.2 kW laser", J.Phys. D: Appl.Phys. 30, 1103 (1997). CrossRef E.A. Trubacheev, Trudy FIAN 102, 3 (1977). G.M. Grigorian, B.M. Dymshits and Yu.Z. Ionikh, "Influence of oxygen on the parameters of the active medium in an electric-discharge CO laser", Sov J Quant Electron 19, 889 (1989). CrossRef V.N. Ochkin, S.Yu. Savinov, N.N. Sobolev and E.A. Trubacheev, Kvant. Elektr. 1, 573 (1974).